Decision Support System for KIP Universitas Global Jakarta Scholarship Recipients Using the Simple Additive Weighting (SAW) Method - Harjiyanto, Kun; Ekawati, Risma; Anjara, Febria; Jaenul, Ariep (Universitas Negeri Padang, 2024)
In accordance with the explanation of article 76 UU No.12 Tahun 2012 about Higher Education. In article 76 Paragraph 1 Explained that,